Prevention of stroke and cognitive decline in pediatric population in resource-limited settings - Itanyi, Ukamaka Dorothy; Nnodu, Obiageli Eunice (Frontiers in Stroke, 2024)
There is an increasing global burden of pediatric stroke especially in low-and middle-income countries (LMICs). This is worsened by the specific risk factors in these areas, including Sickle Cell Disease and endemic infections like Tuberculosis and Human Immunodeficiency disease.Stroke occurs 221 to 300 times more frequently in patients with SCD when compared to healthy children. Although established stroke units and acute stroke care can improve outcomes, these are often not available in resource-poor settings. Primary and secondary prevention of strokes become a very important strategy to reduce the mortality and debilitating physical and cognitive long-term effects of stroke.There are myriads of challenges with implementing already established global policies and guidelines for stroke care in LMICs. These include paucity of data on this subject, poor knowledge and awareness about the symptoms of childhood stroke, adverse cultural beliefs regarding strokes, lack of screening and diagnostic equipment, inadequately trained manpower as well as nonexistent evidence-based management guidelines in these regions.To address these challenges, simple, cost-effective, stroke care models that determine the process of care and how available services should be delivered have been proposed to suit the peculiarities of LMICs in the areas of stroke risk assessment, prevention, and management.